Bigger, faster, stronger - Shepard, Greg 1942-; Goss, Kim 1956- (Human Kinetics, 2017)
Bigger Faster Stronger (BFS) remains the premier training program for high school and college athletes. The third edition of the Bigger Faster Stronger book includes the latest research; training protocols for strength, speed, power, flexibility, balance, and agility; and new content on balance, safety, and plyometrics.